The Problem of Vertical and Horizontal Identity in Intergenerational Relationships - Simonyan, Hamlet (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
Philosophical ideas aimed at establishing and fostering equitable and constructive relationships between generations are gradually gaining more attention. From a philosophical perspective, the study of ethical problems related to intergenerational relations presents an opportunity to raise a number of pivotal questions and their potential solutions, questions that encompass issues such as identity of generations, transmission of socio-cultural heritage from generation to generation, intergenerational justice, responsibility between generations, etc. In this context, it is important to keep in mind that topics concerning different generations and generally having an intergenerational component imply diversity in some sense since we are dealing with the axiological and worldview features of different generations.Considering the above, the article discusses the process of constructing the identity of generations, explicitly addressing the gaps and contradictions between vertical (temporal) and horizontal (spatial) identity nowadays. Analyzing the features of vertical identity and horizontal identity of generations, the article draws from past experiences, identity metanarratives, and their integration into the identity-constructing process.The work also analyzes the role and significance of postmemory in shaping the identity and experiences of generations, highlighting both its constructive and destructive aspects.
Keywords: identity; generations; intergenerational relationships; vertical identity; horizontal identity; postmemory; metanarratives; past